Teachers’ Evaluation Concepts and Practices in STE Curricular Area in Public Secondary Schools in Arequipa (Peru) (Revista Peruana de Investigación Educativa, 2011)
Teachers in the curricular area of Science, Technology and Environment (STE), in the course of their educational interventions, reveal a set of conceptions and assessment practices that are not always consistent with the purposes of educational renewal. In their being and acting, teachers have thoughts and actions that respond to speeches and internalized routines because of their continuous training. Specifically, there are “traditional” ways of evaluating, such as evaluative purposes focusing on the adoption of learning goals (achievement) with the symbolic functions of evaluation, prioritizing the use of current regulations, the prevalence of conceptual contents over others, the recurrence of evaluation procedures focused on solving and expository capacities, but in detriment of other resources based on observation and reflection, and teacher responsibility as an evaluator; along with “modern” postures that act as reference to the others, a preference for an extensive assessment, relegating normative evaluation and adopting a criterial one.
Keywords: Secondary Education; science education; learning assessment; secondary teacher; teaching responsibility